NATURAL INHIBITOR OF AGRONOMICALLY REPELLENT PLANT TOWARDS CLINICAL ISOLATE OF CHLORAMPHENICOL RESISTANT-SALMONELLA TYPHI - KUSUMA, SRI AGUNG FITRI; HERAWATI, IRMA ERIKA; RAMDHANI, DANNI; MAULANA, BAGUS (International Journal of Applied Pharmaceutics, 2022)
Objective: This study was purposed to determine the most effective inhibition among those repellent plants i.e. The leaves of kirinyuh (Chromolaena odorata), kenikir (Cosmos caudatus), bandotan (Ageratum conyzoides), grass teki (Cyperus Cyperus rotundus), lemongrass (Cymbopogon citratus) and suren (Toona sureni) towards S. typhi clinical isolate. Methods: The ethanolic extracts of sixt plants were obtained by maceration method using 70% ethanol. Phytochemical screening was done using the standard methods as described by Farnsworth. The inhibition of the repellent leaves ethanolic extracts to chloramphenicol resistant-S. typhi clinical isolate assayed using the agar diffusion method and statistically analyzed by ANOVA followed by the Duncan test. The most potential plant was further determined by investigating the minimal inhibitory concentration (MIC) and minimal bactericidal concentration (MBC) value using the microdilution test. Results: As the result, all ethanolic leaves extracts contain alkaloids, flavonoids, and tannins, except that tannins were not found in C. rotundus and A. conyzoides. However, all extracts had the activity to inhibit the growth of S. typhi. T. sureni leaves extract evidently showed the strongest inhibition with MIC value in the range of 1.5625<x≤3.125 mg/ml and the MBC value in the range of 6.25<x≤12.5 mg/ml. The ratio of MBC/MIC≤4, thus, T. sureni leaf extract may be classified as a strong bactericidal agent. Conclusion: In summary, T. sureni extract leaves achieved the most appreciable value of MIC MBC and considered as the bactericidal agent which has strong potential to be a novel anti-typhoid fever agent.